Clinicopathological manifestations of coexistent monoclonal immunoglobulin deposition disease and immunotactoid glomerulopathy - Wang, Yina; Yan, Yu; Dong, Bao; Zou, Wanzhong; Li, Xin; Shao, Chunying; Jiang, Lei; Wang, Mei; Zuo, Li (Frontiers in Medicine, 2022)
Combination of monoclonal immunoglobulin deposition disease (MIDD) and immunotactoid glomerulopathy (ITG) is a rare form of monoclonal immunoglobulin (MIg)-associated renal disease. We retrospectively reviewed the native kidney biopsy specimens at Peking University People's Hospital from 2011 to 2020. Five patients were diagnosed as MIDD+ITG. Their clinical and pathological characteristics were studied. The typical clinical features were nephritic syndrome and renal dysfunction with prominent anemia, but hematuria was mild. Under light microscopy, segmentally or globally distributed mesangial nodular sclerosis was the major lesion. Other lesions, including mesangial matrix hyperplasia and membranoproliferative glomerulonephritis-like lesion, might be presented at the same time and in the same glomeruli. The electronic microscopy and immunofluorescence have greatest value in the diagnosis of MIDD+ITG. Under immunofluorescence, MIg, usually monoclonal light chains, deposited along glomerular basement membranes and tubular basement membranes, while the intact MIg or monoclonal heavy chain deposited in the mesangial regions. Corresponding to the depositions on immunofluorescence, punctate “powdery” deposits along glomerular basement membranes and tubular basement membranes were revealed under electronic microscopy indicating the presence of MIDD. And microtubular substructures (diameters of 20-50 nm) exhibiting hollow cores arranged in parallel arrays in mesangial regions were found, indicating the presence of ITG. Patients treated with bortezomib-based regimen seemed to have better outcomes. In conclusion, MIDD+ITG is a rare combination form of MIg-associated renal disease. Accurate diagnosis requires the comprehensive pathological investigations.